ANALISIS HUBUNGAN KAUSALITAS ANTARA COMPUTER ANXIETY, PENGALAMAN KOMPUTER (COMPUTER EXPERIENCE) DAN KEMAHIRAN KOMPUTER (Studi pada Mahasiswa Politeknik Negeri Sriwijaya) - Heri Setiawan (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2012)
This research was done at Polytechnic State of Sriwijaya and aimed at understanding the Influences of computer anxiety and computer experience on computer self-efficacy.. This study uses data collected by a survey on active student at Polytechnic State of Sriwijaya, using simple random sampling method with amount of sample 100 respondent. The data analysis using SPSS software and AMOS. The independent variables are computer anxiety and computer experience. Dependent variable is computer self-efficacy. The study results indicate that computer anxiety had significant and negative influence on computer self-efficacy. Then, computer experience had significant and positive influence on computer self-efficacy.